CHARACTERISTICS OF THE LIFE OF PATIENTS WITH DIABETES - Поддубная, Антонина; Гончарук, Людмила; Маковийчук, Кристина (Modern engineering and innovative technologies, 2022)
The article highlights the features of the life of patients with diabetes, namely life situations against the background of diabetes, and discusses practical advice for people with diabetes who want to lead a full, eventful life.